Profile of Self-Regulated Learning of Students on Online Mathematics Learning: Profil Self-Regulated Learning Siswa pada Pembelajaran Matematika Secara Daring - Khotimah, Husnul; Aini, Layla Nurul; Sari, Tri Hariyati Nur Indah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
Self-regulated learning is the ability to direct and control oneself in thinking and acting and not feeling emotionally dependent on others. This study aims to determine the elements of online mathematics learning that cause students' self-regulated learning to strengthen and weaken. This type of research is a quantitative description with a population of all students of class VIII which is then selected by respondents as many as 67 students. The data was obtained through the distribution of questionnaires with google form. Based on the research conducted, it is known that the three elements of online mathematics learning that strengthen students' self-regulated learning are efforts to find learning resources, re-examine assignments before they are collected, and have targets to be achieved in the learning process. Meanwhile, the three elements of online mathematics learning that weaken students' self-regulated learning are group learning, help from friends when solving problems, and studying when there are exams.